Accurate Visual Metrology from Single and Multiple Uncalibrated Images - Criminisi, Antonio (University of Oxford, 2000)
Introduction: Accurate Measurements from Images. Why use Vision? Why is Visual Metrology Hard? Applications and Examples. Summary.- Related Work: Introduction. Using Images for Measuring and Reconstruction.- Background Geometry and Notation: Introduction. Notation. Camera Models and Perspective Mappings. Radial Distortion Correction. Vanishing Points and Vanishing Lines. Uncertainty Analysis.- Metrology on Planes: Estimating the Homography. Uncertainty Analysis. Application - A Plane Measuring Device. Duality and Homologies. Single View Metrology: Introduction. Geometry. Algebraic Representation. Uncertainty Analysis. Three-Dimensional Metrology from a Single View. Applications. Missing Base Point.- Metrology from Planar Parallax: Introduction. Background. Geometry and Duality. Scene Reconstruction. Uncertainty Analysis.- Gallery of Examples: Introduction. Reconstruction from Photographs. Reconstruction from Paintings. Discussion.- Conclusion: Summary. Discussion. Future Work.- Metrology on Planes, Computing Homography Uncertainty.- Maximum Likelehood Estimation of End Points for Isotropic Uncertainties.- Single View Metrology, Variance of Distance Between Planes.- Single View Metrology, Variance of the Affine Parameter alpha.- Metrology form Planar Parallax, Derivations.- Metrology form Planar Parallax, Variance of Distances.- Index.
PhD (DPhil) thesis